Enhancing Quadratic Function Learning Outcomes with TGT Cooperative Learning, Desmos, and Quizwhizzer - Khoirida Hardini Kurniani; Kriswandani Kriswandani; Anna Royyana Nikmah (EduMa: Mathematics education learning and teaching, 2023)
This collaborative action research, CAR, aimed to improve the learning outcomes within the material of quadratic function with TGT typed cooperative method, assisted by desmos and quizwhizzer for X-9 graders of SMA N 3 Salatiga. The subjects were the X-9 graders, consisting of 34 participants, 14 males and 20 females. The research lasted from precycle, cycle I, and cycle II. Each cycle consisted of four stages: planning, applying, observing, and reflecting. The data collecting techniques were learning outcome test, observation, and documentation. The applied research instruments were observation sheet for the learning process and questions for each end of cycle. The researchers analyzed the data with descriptive statistics and qualitative description. The results showed the applied model with desmos and quizwhizzer assistances could improve the learning outcomes. The obtained mean scores increased, starting from the pre-cycle with 68.8, cycle II with 75.3, and cycle II with 82.6. The classical achievement was 80%. The achievement increased from the precycle with 47.1%, cycle I with 70.6%, and cycle II with 85.3%.